(untitled) (Community Based Medical Journal, 2022)
A cross-sectional study was conducted in the Department of Radiology & Imaging, in collaboration with the Department of Obstetrics & Gynaecology, in Dhaka Medical College Hospital and Bangabandhu Sheikh Mujib Medical University Hospital, Dhaka, Bangladesh, between July 2010 and March 2012, to evaluate the diagnostic usefulness of transvaginal color doppler ultrasonography (TVCDU) in differentiating benign and malignant uterine tumours. A total of fifty women, diagnosed as having uterine tumours both clinically and using ultrasound, participated in the study. They were evaluated preoperatively using TVCDU. All the study participants underwent surgical operation and resected specimens were sent for histopathological examination. Histopathology reports were correlated with the of colour Doppler findings. The mean age of the patients was 47.72±8.79 years. Major complaints were menorrhagia (58%), dysmenorrhoea (50%) and lump in the lower abdomen (48%). Neovascularization was found in 16(32%) cases. The mean resistance index and pulsatility index were much lower in malignant tumours than that of the benign counterpart (0.35±0.03 vs. 0.67±0.01 and 0.65±0.14 vs. 1.35±0.11 respectively); the difference was statistically significant (P<0.001). The sensitivity, specificity, positive and negative predictive values of TVCDU were found 86.7%, 97.14%, 92.85% and 94.4% respectively. Overall diagnostic accuracy was 94%. To summarize, blood flow characteristics of benign and malignant uterine tumours, as evident on color Doppler imaging, have distinct diagnostic value. Hence, transvaginal colour Doppler ultrasound examination can be used as an easily available, efficient, and non-invasive diagnostic modality in differentiation of uterine tumours, which can be histologically confirmed later. CBMJ 2021 January: vol. 10 no. 02 P: 105-110